Integument in Antarctic seals: A comparative study and its relation to extreme environments - Krmpotic, Cecilia Mariana; Loza, Cleopatra Mara; Negrete, Javier; Scarano, Alejo Carlos; Carlini, Alfredo Armando; Guerrero, Alicia; Barbeito, Claudio Gustavo (Acta Zoologica)
Due to the semiaquatic lifestyle of seals and the extreme climates they inhabit, their integumentary system has aroused the curiosity of several authors for more than a century. The aim of this contribution was to perform an exhaustive histological de- scription of the integument Antarctic seals through different methodological ap- proaches in a comparative framework. The species considered include the iceobligate?Weddell (Leptonychotes weddellii) and leopard (Hydrurga leptonyx) seal?and the icetolerant, and southern elephant seal (Mirounga leonina). In addi- tion, we attempted to link the histological features to their different lifestyles. All three species showed features related to their amphibious lifestyle (i.e., parakeratotic epidermis with abundant melanin granules, dermis with numerous arteriovenous anastomoses and a great amount of elastic fibres). In aquatic mammals, parakeratosis would decrease cellular replacement, the great amount of melanin is related to the high exposure to solar radiation, the presence of arteriovenous anastomoses is related to thermoregulatory mechanisms, and the presence of elastic fibres is due to varia- tions of thickness in the adipose tissue that requires high elasticity of the dermis. Fil: Krmpotic, Cecilia Mariana. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. División Paleontología Vertebrados; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Veterinarias. Departamento de Ciencias Básicas. Cátedra de Histología y Embriología; Argentina Fil: Loza, Cleopatra Mara. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Veterinarias. Departamento de Ciencias Básicas. Cátedra de Histología y Embriología; Argentina. Universidad Nacional de la Plata. Facultad de Ciencias Naturales y Museo. ...